ANALISIS PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT MITSUBA INDONESIA PIPE PARTS DI BEKASI JAWA BARAT - Marman Marman; Ida Betanursanti (Universitas Ahmad Dahlan Indonesia, 2013)
This research aim to know the relationship between physiological needs, safety needs, social needs and productivity of the workers and Mitsuba Indonesia Pipe Parts Ltd. The method of this research is questioner of 40 respondents. Then the data calculate with inferential statistics and multiple linear regression. The result of this research is an equation of correlation between physiological needs, safety needs, social needs and productivity : Y = ln (0.4296537) + 0.00044267.ln (ð‘‹1) + 0.00115069.ln (ð‘‹2) + 0.00118606.ln (ð‘‹3) with the wrong 0,00096878%. This equation shown that all the variable had correlation each other. Key words : physiological needs, safety needs, social needs and productivity